Sinergitas Dinas Sosial Provinsi Bali Dengan Panti Sosial Asuhan Anak (PSAA) Udyana Wiguna Dalam Penanganan Anak Terlantar Di Kabupaten Buleleng - I Gusti Ayu Diah Mahadewi Sastrawan; I Putu Dharmanu Yudartha; Putu Nomy Yasintha (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
Neglected children also have the right to live and participate as part of the citizens in accordance with human dignity, and to receive protection from violence and discrimination. Handling neglected children is one of the government's tasks in the social sector which must be handled properly so that these children can live a more decent life and have their rights fulfilled. The Provincial Government of Bali in dealing with the problems of neglected children cooperates with the UPTD Social Services and the Udyana Wiguna Children's Orphanage. This study aims to find out how the synergy is between the Bali Province Social Service, the UPTD Social Services and the Udyana Wiguna Children's Orphanage. This study uses descriptive qualitative methods with data collection techniques, namely observation, interviews and documentation. The results of this study were analyzed using three indicators of synergy according to Stephen R. Covey, namely cooperation, communication and coordination which showed that the synergy that exists between the Bali Province Social Service, the UPTD Social Services and the Udyana Wiguna Children's Orphanage has gone well in terms of the handling and care of neglected children carried out by these three institutions which has resulted in a significant reduction in the number of abandoned children in Buleleng Regency. However, there are still some deficiencies in the handling process, such as the absence of outreach to the community and the lack of financial support from the government. These deficiencies must be improved so that the synergy that exists can run more optimally.